Ethics on the line: How obedience pressure shapes auditors’ decisions - Eko Yulianto; Retna Sari (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara)
This study examines the influence of professional skepticism and obedience pressure on auditors’ ethical formulation of audit opinions. Encompassing central and regional offices, 243 auditors from the Audit Board of Indonesia participated in this experimental study. In the scenario, a junior audit manager discovered a misstatement in fixed asset accounts; obedience pressure was simulated by imposing career advancement threats if the auditor did not ignore the error. Binary logistic regression was employed to predict the likelihood of issuing an unqualified audit opinion under different conditions. Obedience pressure significantly reduced ethical decision-making, with auditors more likely to follow superior orders even when such orders compromised ethical standards. In contrast, professional skepticism, as a standalone factor, did not significantly influence ethical decisions. However, its interaction with obedience pressure exhibited a marginal effect, implying that greater skepticism may somewhat mitigate the adverse influence of obedience pressure. These findings highlight the complex interplay between organizational influence and individual traits in auditing practices, as well as the ethical risks faced by professional auditors. The study's novelty lies in its use of practicing auditors as participants, in contrast to earlier research involving students or non-practitioners, allowing for a more realistic assessment of how skepticism operates in actual audit settings.